2016
DOI: 10.2147/jpr.s114915
|View full text |Cite
|
Sign up to set email alerts
|

Impaired psychomotor ability and attention in patients with persistent pain: a cross-sectional comparative study

Abstract: Background and aimsPatients with pain have shown cognitive impairment across various domains. Although the pain qualities vary among patients, research has overlooked how cognitive performance is affected by the duration and persistence of pain. The current study sought to fill this gap by examining how qualitatively different pain states relate to the following cognitive functions: sustained attention, cognitive control, and psychomotor ability.Patients and methodsPatients with musculoskeletal pain in primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The individuals who have regularly current pain have a major impact on decrementing the performance in sustained attention. [ 16 ] Brain parts such as the prefrontal cortex, anterior cingulate cortex, and secondary somatosensory cortex have a major role in controlled and higher-order cognitive processing which involves attention, cognitive control, and certain psychomotor abilities. [ 17 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…The individuals who have regularly current pain have a major impact on decrementing the performance in sustained attention. [ 16 ] Brain parts such as the prefrontal cortex, anterior cingulate cortex, and secondary somatosensory cortex have a major role in controlled and higher-order cognitive processing which involves attention, cognitive control, and certain psychomotor abilities. [ 17 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…50 – 53 Furthermore, research has found a more detrimental effect in cognitive function, as well as in deep tissue pressure pain thresholds, for long-term persistent pain compared to long-term, regularly, recurrent pain. 54 , 55 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the restrictions on movement, the pain that almost always occurs with diseases of the musculoskeletal system can have unfavorable effects on driving behavior. Pain can have a distracting effect on the driver and is associated with impaired psychomotor abilities such as lane- keeping or cognitive performance such as sustained attention [ 190 , 191 ]. Many drivers take analgesics to reduce pain.…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%